HERITAGE CONTESTATION AND CONTEXT OF RELIGION: POLITICAL SCENARIO FROM SOUTHERN ASIA - Singh, Rana P. B. (Politikologija religije, 2008)
Heritage is a cultural identity to be refl ected in the purview of individual, unique and multiple layers of pluralism, especially with respect to religion, at least in Oriental cultures that maintained their traditions and continuity together with examples of contestation, destruction and also sometimes harmonious co-existence. In the span of time the layering of various cultures put their marks, which in the sequence of time turn to be the issue of confl icts due to claims and controls by the diff erent groups. As a consequence there resulted issues of representation, belongingness, control and power, dissonance and contestation. Despite all theoretic constructs and human concerns for peace and harmony the issue of dissonance dominates, especially withreference to ethnicities and religion. The religious built environments are the pitiful suff erers in such happenings of turmoil recorded every parts of the world. In South Asia the Muslim invasion in medieval period (15th to 18th centuries) had been the major force and process for destruction and superimposing Islamic structure, like in case of major sacred cities of Hindus in north India. In the areas of old culture one fi nds heritagescapes that are subject to ‘ill construction and jumbled space’ where ‘several sites appear incompatibly’. The confl icts between secularist democracy and democratic religiosity are the common phenomena in South Asian region. So on, confl icts between archaeological sites or monuments and lived cultural heritage. It may be accepted rationally that if the two communities, Hindus and Muslims, are ready not to heap defeat and humiliation with an aim to re-establish the history of the medieval times, the issues can be resolved amicably. This essay reviews the emerging literature dealing with the enduring role and context of religion in the issue of contesting heritage (mostly cultural). Emphasis is further laid on the contextual constructs of analysis, examples from diff erent parts of Southern Asia, and fi nally role of religion in policies, mitigation and management of contesting heritage.